Street urchins, sociopaths and degenerates : orphans of late-Victorian and Edwardian fiction - Floyd, David (University of Wales Press, 2014)
Taking examples from Gothic, island adventure, imperial, and children's literature, this book addresses the remarkable metaphorical disparity between, and cultural implications of, orphans in late-eighteenth and early-nineteenth British fiction and in more recent instances.